The influence of brand awareness, brand loyalty, and perceived quality on customer satisfaction - Pradinata, I Putu Eka Krisna; Supartha, Anak Agung Ayu Rika Putri (Universitas Pendidikan Nasional, 2022)
Articles[1] Adetunji, R., Nordin, S., & Noor, S. (2014). The Effectiveness of Integrated Advertisement Message Strategy in Developing Audience-Based Brand Equity. Global Business and Management Research: An International Journal, 6(4), 308-318. http://www.gbmrjournal.com/pdf/vol.%206%20no.%204/v6n4-7.pdf[2] Bendixen, M. T. (1993). Advertising Effects and Effectiveness. European Journal of Marketing, 27(10), 19-32. https://doi.org/10.1108/03090569310045861[3] Childers, T. L. and Houston, M. J. (1984). Conditions for a Picture Superiority Effect on consumer Memory. Journal of Consumer Research, September, 643-654.[4] Hardianto, D., & Pratomo, I. A. (2012). Faktor-faktor sistem interaksi yang mempengaruhi efektifitas iklan online. Jurnal Sistem Informasi, 4(1), 26-36. https://doi.org/10.21609/jsi.v4i1.242[5] Kong, S., Huang, Z., Scott, N., Zhang, Z., & Shen, Z. (2019). Web advertisement effectivenessevaluation: Attention and memory. Journal of Vacation Marketing, 25(1), 130-146.https://doi.org/10.1177/1356766718757272[6] Lohtia R, Donthu N, & Hershberger EK. (2003). The impact of content and design elements on banner advertising click-through rates. Journal of Advertising Research, December, 410-418. http://dx.doi.org/10.1017/S0021849903030459[7] Murphy, H., & Duchowski, A. T. (2002). Perceptual gaze extent & level of detail in VR: looking outside the box. ACM SIGGRAPH 2002 Conference Abstracts and Applications, SIGGRAPH 2002.https://doi.org/10.1145/1242073.1242241[8] Negm, E., & Tantawi, P. (2015). Investigating the Impact of Visual Design on Consumers’ Perceptions towards Advertising. International Journal of Scientific and Research Publications, 5(4), 1-9. https://www.semanticscholar.org/paper/Investigating-the-Impact-of-Visual-Design-on-NegmTantawi/5647a61fee3c44c8bac82652b86dac8100e721c9[9] Orquin, J., & Loose, S. (2013). Attention and choice: A review on eye Movements in decision making. Acta psychologica, 144(1), 190-206. https://doi.org/10.1016/j.actpsy.2013.06.003.[10] Posner, M. (1980). Orienting of attention. Quarterly journal of experimental psychology, 32(1), 325. http://dx.doi.org/10.1080/00335558008248231[11] Rayner, K. et al. (2001). How Psychological Science Informs the Teaching of Reading. Psychological Science in The Public Interest, 2(2), 31-74.[12] Shimp, T. A. (2004). Advertising, Promotion, and Supplemental Aspects of Integrated Marketing Communication. Journal of Marketing Communications, 10(4), 289-290 https://doi.org/10.1080/1352726042000250498[13] Sukma, F., Sarma, M., & Syamsun, M. (2015). Efektivitas Iklan dalam Menumbuhkan Brand AwarenessSMA Sampoerna. Jurnal Manajemen Pengembangan Industri Kecil Menengah, 10(2), 182-193.https://doi.org/10.29244/mikm.10.2.182-193[14] Yang, C.-M. (2018). Effects of Message Strategy and Need for Cognition (NFC) on Consumer Attitudes: A Case of Corporate Social Responsibility (CSR) Advertising. Open Journal of Business and Management, 6(July), 714-732. https://doi.org/10.4236/ojbm.2018.63055Books[15] Durianto, S., Widjaja, A. W., & Supratikno, H. (2003). Inovasi Pasar Dengan Iklan Yang Efektif. Erlangga.[16] Jefkins, F. (1991). Modern Marketing Communications. Springer. https://doi.org/10.1007/978-94-011-6868-7[17] Kotler, P. (2000). Marketing Management [Millenium Ed.]. Marketing Management. https://doi.org/10.1016/0024-6301(90)90145-T[18] Kotler, P. (2005). Manajemen Pemasaran. [Jilid 1 dan 2]. PT Indeks Kelompok Gramedia.[19] Kotler, P., & Amstrong, G. (2012). Principles of Marketing Global. Pearson Education.[20] Kotler, P., & Keller, K. L. (2009). Manajemen pemasaran [Jilid 1]. Jakarta.20 - 31VOLUME 3 | NUMBER 1 | APRIL 2022 31[21] Lee, Monle, Johnson, C. (1999). Prinsip-Prinsip Pokok Periklanan dalam Perspektif Global. Kencana Prenada Media Group.[22] Levis, L. R. (2013). Metode Penelitian Perilaku Petani. Ledalero.[23] Mulyana, D. (2010). Komunikasi Nonverbal. In Jurnal Komunikasi.[24] Sobur, A. (2013). Psikologi Umum (Dalam Lintas Sejarah). CV Pustaka Setia. https://doi.org/10.1017/CBO9781107415324.004[25] Sugiyono. (2013). Metode Penelitian Pendidikan Pendekatan Kuantitaif, Kualitatif, dan R&D. Alphabet.[26] Sutisna. (2003). Perilaku Konsumen: Teori dan penerapannya dalam Pemasaran. Ghalia Indonesia.[27] Zimbardo P. (1992). The human choice: Individuation, reason, and order versus deindividuation, impulse, and chaos. University of Nebraska Press.Undergraduate Thesis[28] Puspitasari, I. (2009). Faktor-faktor yang mempengaruhi efektifitas Iklan Dalam Menumbuhkan Brand Awareness [Unpublished undergraduate thesis]. Universitas Diponegoro.Website[29] Alexa.com (2020, September). Chart of percentage traffic from search in September 2020.https://www.alexa.com[30] Tribunnews.com (2020, September). Image of the advertisement on Tribunnews.com website page. https://www.tribunnews.com